Online digital platform use by adolescents in Kenya. Issue 2 (3rd April 2022) - Oloo, Ong'ong'a Daniel
ABSTRACT: This study explored internet use by adolescents, aged 12–14 years, who reported negative online experiences in Kenya. A qualitative case study method was employed, using in-depth interviews and thematic analysis. The study's findings show that young people frequently used online platforms at night for entertainment (online gaming, betting, chatting, and streaming content) and educational purposes (searching for educational content). The challenges they encountered included fraud, stalking, pop-ups, and accidental access to adult content. They devised strategies for staying safe that included going offline, ignoring messages, deleting accounts, and hiding online (e.g. fake photos or IDs). Study findings indicate that female users more readily reported issues they encountered online than males. The study suggests the need for strategic partnerships between relevant international and local stakeholders to create awareness and empowerment programs (training, advocacy, and resourcing) to address online risks through the media, formal school programs, and parent–teacher associations. IMPACT SUMMARY a. Prior State of Knowledge: While adolescents' digital platform use has been studied extensively in other countries, little is known about the online behaviors of African adolescents in general and Kenyan adolescents in particular. b. Novel Contributions: This study responds to the public dialogues on the security and safety of adolescents using internet resources in Kenya and elsewhere by providing empirical data on the internet safety of adolescents in Kenyan schools. c. Practical Implications: Stakeholders are encouraged to form strategic international and local partnerships to create awareness, implement empowering training programs, as well as advocate and provide resources through the media, parent–teacher associations, and formal school programs that address adolescents' online risks.